Reflective heat-insulation rock slice real stone paint as well as preparation method and application thereof
By adding modified titanium-based particles and modification additives to the reflective heat-insulating composite rock flakes, a multi-porous structure and a cross-linking network is formed, which solves the problems of uneven distribution of reflective heat-insulating materials, insufficient bonding strength, poor water-repellent, weather-resistant and pollution-resistant properties of existing reflective heat-insulating real stone paint, and achieves efficient reflective heat-insulating, water-repellent and stain-resistant self-cleaning properties.
Patent Information
- Application Number
- CN202510316471.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The existing reflective heat-insulating real stone paint has problems such as uneven distribution of reflective heat-insulating materials, insufficient bonding strength, poor water repellent, weather-resistant and pollution-resistant properties, which leads to problems such as cracking, peeling and degradation of reflection during use.
A reflective and heat-insulated rock flake real stone paint is used, and its raw materials include reflective and heat-insulated color paste, reflective and heat-insulated composite rock flakes and base paint. By adding modified titanium-based particles and modification additives to the reflective and heat-insulated composite rock flakes, a multi-porous structure and cross-linking network are formed to enhance its emission insulation, water repellent and stain-resistant self-cleaning properties.
It has achieved excellent reflective performance under high brightness environment, reduced water absorption of coating, improved hydrophobic self-cleaning, avoided cracking, peeling and reduced reflective ability, and has excellent application prospects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of building exterior wall decoration materials, and in particular to a reflective heat-insulating rock flake real stone paint and a preparation method and application thereof. Background Art
[0002] In recent years, with the acceleration of urbanization and the improvement of people's living standards, the demand for building exterior wall decoration materials has been growing. Although traditional exterior wall decoration materials such as tiles and marble are beautiful and durable, they have problems such as complex construction, high cost, easy to fall off, and do not have energy-saving characteristics. In contrast, real stone paint, as a new type of environmentally friendly exterior wall decoration material, is favored by the market because of its low resource consumption, easy construction and renewal, no safety hazards, and rich colors and varieties. Especially in the context of energy conservation and emission reduction becoming a social consensus, the research and development of real stone paint with reflective heat insulation functions is particularly important.
[0003] At present, there are some reflective heat-insulating real stone paint products on the market, which enhance the coating's ability to reflect solar radiation heat by adding specific reflective heat-insulating materials. However, existing reflective heat-insulating real stone paints still face some problems, such as: the reflective heat-insulating materials of some products are unevenly distributed, resulting in low overall reflectivity and failure to fully reduce the surface temperature of buildings; the bonding strength of some reflective heat-insulating real stone paints on different substrates is not ideal, especially in extreme climatic conditions, and may peel off; the water-repellent, weather-resistant and pollution-resistant properties are poor, and the reflective ability is greatly reduced when the coating is polluted.
[0004] Therefore, in order to effectively solve the above problems, the present application provides a reflective and heat-insulating rock flake real stone paint and a preparation method thereof. The rock flake real stone paint finally prepared by the present application can not only meet the existing consumers' demand for the beauty and reflective heat insulation of building exterior wall decoration materials, but also maintain excellent water-repellent, weather-resistant, stain-resistant and self-cleaning properties; in particular, it can maintain excellent reflective performance in a high-brightness environment, reduce the water absorption of the coating, improve the hydrophobic self-cleaning property, and effectively avoid the problems of cracking, peeling and reduced reflectivity of the existing real stone paint during use, and has a very excellent application prospect. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a reflective heat-insulating rock flake real stone paint. The raw materials, calculated by mass percentage, are: 1~8% reflective heat-insulating color paste, 5~15% reflective heat-insulating composite rock flakes, 20~35% base paint, and colored sand to make up the balance.
[0006] As a preferred solution, the mass ratio of the reflective heat-insulating color paste, the reflective heat-insulating composite rock sheet and the base paint is (2-5): (5-10): (25-30).
[0007] As a preferred solution, the mass ratio of the reflective heat-insulating color paste, the reflective heat-insulating composite rock sheet and the base paint is (3-4): (7-9): (26-28).
[0008] As a preferred solution, the raw materials of the reflective heat-insulating color paste, measured in mass percentage, are: 20-30% reflective heat-insulating pigment, 3-5% dispersant I, 1.5-2.5% wetting agent I, 1-3% cellulose ether I, 0.5-0.8% defoaming agent I, 2-2.5% film-forming aid I, 0.3-0.5% rheological aid I, and the balance is made up of deionized water.
[0009] As a preferred solution, the dispersant I is polyvinyl pyrrolidone or polycarboxylate.
[0010] As a preferred solution, the dispersant I is polyvinyl pyrrolidone.
[0011] As a preferred solution, the wetting agent I is ethylene bisstearamide or polyoxyethylene glyceryl tristearate.
[0012] As a preferred solution, the wetting agent I is ethylene bisstearamide.
[0013] As a preferred solution, the cellulose ether I is at least one of hydroxyethyl cellulose ether, hydroxypropyl cellulose ether and hydroxyethyl methyl cellulose ether.
[0014] As a preferred solution, the cellulose ether I is hydroxyethyl cellulose ether.
[0015] As a preferred solution, the film-forming aid I is at least one of dodecyl alcohol ester, hexadecanol ester and sorbitan tristearate.
[0016] As a preferred solution, the film-forming aid I is dodecanol ester.
[0017] As a preferred solution, the rheological additive I is organic modified bentonite or sodium polyacrylate.
[0018] As a preferred solution, the rheological additive I is sodium polyacrylate.
[0019] As a preferred scheme, the raw materials of the reflective heat-insulating composite rock sheet, measured in mass percentage, are: 6-10% reflective heat-insulating pigment, 10-12% aluminum silicate, 20-30% composite solid material, 30-35% aqueous acrylic emulsion, 8-10% aqueous polyurethane emulsion, 0.2-0.5% cellulose ether ⅠⅠ, 0.3-0.6% dispersant ⅠⅠ, 0.1-0.2% wetting agent ⅠⅠ, 0.2-0.3% pH adjuster, 0.3-0.7% defoamer, 0.3-0.5% bactericidal and mildewproof agent, 0.5-1% polysiloxane, 1-2% film-forming aid ⅠⅠ, 0.1-0.3% rheological aid ⅠⅠ, and the balance is made up of deionized water.
[0020] As a preferred solution, the composite solid material is a composition of talcum powder, heavy calcium carbonate and modified titanium-based particles.
[0021] As a preferred solution, the mass ratio of the talc powder, heavy calcium carbonate and modified titanium-based particles is (6-10): (10-15): (8-14).
[0022] As a preferred solution, the mass ratio of the talc powder, heavy calcium carbonate and modified titanium-based particles is (8-9): (11-13): (9-11).
[0023] As a preferred solution, the average particle size of the talc is 1.5-2 μm.
[0024] As a preferred solution, the average particle size of the heavy calcium carbonate is 0.5-1.5 μm.
[0025] As a preferred solution, the preparation method of the modified titanium-based particles specifically includes the following steps: S1: adding titanium dioxide, zinc oxide, succinic anhydride and γ-aminopropylmethyldiethoxysilane to a N,N-dimethylformamide solvent to obtain pretreated particles; S2: adding the pretreated particles, tetrabutyl titanate and 1,4-naphthalene dicarboxylic acid to a N,N-dimethylacetamide solvent, adding 2-methylimidazole, p-aminobenzoic acid and hydrofluoric acid to continue the reaction; S3: cooling to room temperature after the reaction is completed, centrifugally filtering to obtain a solid product, washing with N,N-dimethylformamide and deionizing cycles, and vacuum drying to obtain the product; As a preferred solution, the preparation method of the modified titanium-based particles specifically includes the following steps: S1: titanium dioxide, zinc oxide, succinic anhydride and γ-aminopropylmethyldiethoxysilane are mixed and added to N,N-dimethylformamide solvent, and ultrasonically dispersed at 400-500W for 30-35min, then heated to 65-70°C, ultrasonically insulated for 2-2.5h, then centrifuged and filtered, washed with ethanol and dried to obtain pretreated particles; S2: pretreated particles, tetrabutyl titanate and 1,4-naphthalenedicarboxylic acid are mixed and added Add to N,N-dimethylacetamide solvent, heat to 50-60°C and ultrasonically disperse at 400-500W for 30-35min, then heat to 90-95°C and keep warm for 5-6h, add 2-methylimidazole, p-aminobenzoic acid and hydrofluoric acid, heat to 110-120°C and keep warm for 13-16h; S3: After the reaction is completed, cool to room temperature, centrifuge to obtain a solid product, wash with N,N-dimethylformamide and deionized water for 2-3 times, and then vacuum dry at 80-85°C for 8-10h.
[0026] As a preferred solution, the average particle size of the titanium dioxide is 10-15 nm.
[0027] As a preferred solution, the mass ratio of titanium dioxide, zinc oxide, succinic anhydride and γ-aminopropylmethyldiethoxysilane is (1-1.2): (0.1-0.2): (0.3-0.4): (0.05-0.1).
[0028] As a preferred solution, the mass ratio of the pretreated particles, tetrabutyl titanate, 1,4-naphthalene dicarboxylic acid, 2-methylimidazole and p-aminobenzoic acid is (1.2-1.5): (2.5-3): (2.2-2.6): (0.3-0.5): (0.4-0.6).
[0029] In the present application, by adding modified titanium-based particles to the reflective heat-insulating composite rock flakes, the reflective heat-insulating, water-repellent and stain-resistant self-cleaning properties of the rock flake real stone paint can be effectively improved. The added modified titanium-based particles can form a multi-microporous structure with micro-nano particles as the outer wrapping and composite skeleton particles as the inner main body. The existence of this structure can greatly enhance the maintenance effect of the modified titanium-based particles on the surface oxidation molecules, so that in the long-term use process, it can maintain the oxidation and decomposition effect of the real stone paint surface on the organic pollutants, thereby achieving the anti-fouling self-cleaning effect of the real stone paint surface, and the existence of the multi-microporous structure prompts the real stone paint surface to form more gully surface structures, and then in the long-term use process, the surface water molecules are blocked, and the phenomenon of their continuous aggregation to form a continuous surface water layer phase is avoided, so that the surface of the real stone paint cannot promote the penetration of water molecules through the hydration layer, thereby greatly improving its water resistance; on the other hand, the complex skeleton structure formed can greatly improve the electronic vibration effect of the surface titanium dioxide particles, thereby greatly improving the overall infrared refractive index of the modified titanium-based particles, inhibiting its subsequent conversion efficiency of photothermal energy, and increasing the light penetration resistance through its scattering phenomenon of light, improving the reflection efficiency, and thus obtaining good reflective heat insulation performance.
[0030] As a preferred solution, the solid content of the aqueous polyurethane emulsion is 35-42%.
[0031] As a preferred solution, the viscosity of the aqueous polyurethane emulsion is 1000-3000 mPa·s, and the temperature condition is 25°C.
[0032] As a preferred solution, the cellulose ether II is at least one of hydroxypropyl methyl cellulose ether, hydroxypropyl methyl cellulose ether or carboxymethyl cellulose ether.
[0033] As a preferred solution, the cellulose ether II is hydroxypropyl methyl cellulose ether.
[0034] As a preferred solution, the dispersant Ⅱ is polycarboxylic acid ammonium salt or acrylic acid sodium salt.
[0035] As a preferred solution, the dispersant Ⅱ is a polycarboxylate ammonium salt.
[0036] As a preferred solution, the wetting agent Ⅰ is at least one of PEG-20 oleate, polysorbate 80 and polyoxyethylene glyceryl tristearate.
[0037] As a preferred solution, the wetting agent Ⅱ is polysorbate 80.
[0038] As a preferred solution, the film-forming aid Ⅱ is at least one of dodecyl alcohol ester, hexadecanol acetate and propylene glycol phenyl ether.
[0039] As a preferred solution, the film-forming aid Ⅰ is hexadecyl alcohol acetate.
[0040] As a preferred solution, the rheological additive ⅠⅠ is at least one polyurethane rheological additive.
[0041] As a preferred solution, the reflective insulation pigment in the reflective insulation color paste and the reflective insulation composite rock sheet raw material is at least one of titanium dioxide W800, iron oxide yellow, cobalt green, cobalt blue, titanium nickel yellow, zinc iron yellow and chrome iron black.
[0042] As a preferred solution, the reflective heat-insulating pigment in the reflective heat-insulating color paste and the reflective heat-insulating composite rock sheet raw material is at least one of titanium dioxide W800, iron oxide yellow, titanium nickel yellow, zinc iron yellow and cobalt blue.
[0043] As a preferred solution, the base paint comprises, by mass percentage, 48-50% aqueous acrylic emulsion, 0.2-0.3% pH adjuster, 0.2-0.5% bactericidal and mildewproof agent, 1-2% polysiloxane, 0.2-0.5% defoaming agent, 0.6-1% cellulose ether ⅠⅠⅠ, 2.5-3% film-forming aid ⅠⅠⅠ, 0.1-0.5% rheological aid ⅠⅠⅠ, 0.2-0.5% antifreeze agent, 0.5-1.5% modification aid, and the balance is made up of deionized water.
[0044] As a preferred solution, the cellulose ether III is hydroxyethyl methyl cellulose ether.
[0045] As a preferred solution, the film-forming aid Ⅲ is at least one of hexadecyl alcohol acetate, propylene glycol phenyl ether or dodecyl alcohol ester.
[0046] As a preferred solution, the film-forming aid Ⅲ is propylene glycol phenyl ether.
[0047] As a preferred solution, the rheological additive Ⅲ is sodium polyacrylate.
[0048] As a preferred solution, the antifreeze agent is a combination of diethylene glycol and propylene glycol.
[0049] As a preferred solution, the mass ratio of diethylene glycol to propylene glycol is (4-5): (1-1.5).
[0050] As a preferred solution, the preparation method of the modified auxiliary agent specifically includes the following steps: S1: adding octamethylcyclotetrasiloxane to deionized water, heating and stirring; S2: after the stirring is completed, adding aminopropyl triethoxysilane and sodium dodecyl sulfate, γ-methacryloxypropyl trimethoxysilane, isobornyl acrylate and glycidyl methacrylate in sequence, stirring for reaction, adding benzoyl peroxide, and keeping the temperature for reaction; S3: after the reaction is completed, slowly adding ammonia water, controlling the pH value of the system to 7.5-8, then naturally cooling to room temperature, sieving the product, washing, and obtaining; As a preferred solution, the preparation method of the modified auxiliary agent specifically comprises the following steps: S1: adding deionized water to a high-speed stirrer, stirring at room temperature for 5 to 10 minutes at a speed of 800 to 1000 rpm, ensuring that the water temperature is moderate, adding octamethylcyclotetrasiloxane, heating to 60 to 65°C, and stirring at a speed of 400 to 800 rpm for 30 to 40 minutes; S2: after the stirring is completed, adding aminopropyl triethoxysilane and sodium dodecyl sulfate in sequence, adding 400 to 800 rpm each time. Stir at a speed of rpm for 15-20 minutes, then add γ-methacryloxypropyltrimethoxysilane, isobornyl acrylate and glycidyl methacrylate in sequence and continue stirring for 30-35 minutes. After stirring, heat to 80-90°C, add benzoyl peroxide, and keep warm for reaction for 3-5 hours; S3: After the reaction is completed, slowly add ammonia water to control the pH value of the system to 7.5-8, then cool naturally to room temperature, filter the product through a 500-600 mesh sieve, wash with ethanol, and obtain it after completion.
[0051] As a preferred solution, the mass ratio of octamethylcyclotetrasiloxane, aminopropyltriethoxysilane and sodium dodecyl sulfate is (25-30): (15-20): (5-6).
[0052] As a preferred embodiment, the mass ratio of octamethylcyclotetrasiloxane, γ-methacryloxypropyltrimethoxysilane, isobornyl acrylate and glycidyl methacrylate is (25-30): (7-10): (5-8): (5-8).
[0053] In the present application, the addition of the modification auxiliary agent can realize the repulsion of water molecules inside the real stone paint through the siloxane and acrylate long chains and corresponding groups contained therein, reduce the penetration rate of water, and increase the penetration resistance. On the other hand, it is easier to form a barrier film layer. The presence of this film layer can not only achieve a barrier effect on water molecules in the system, but also reduce the humidity of the system. The more solid multi-level cross-linked network formed by it can form microchemical bonds with other raw materials of real stone paint, fully increase the mutual viscosity between molecular chains, thereby greatly improving the resistance of the real stone paint system to molecular chain slippage during use, enhancing the overall toughness and mechanical properties, and reducing the fracture caused by molecular chain slippage, thereby ensuring the anti-cracking and anti-flaking properties of the real stone paint, and ensuring the stability of the reflective heat insulation properties.
[0054] As a preferred solution, the solid content of the water-based acrylic emulsion in the reflective heat-insulating composite rock sheet and the base paint raw material is 45-52%, the viscosity is 2500-4000 mPa·s, and the temperature condition is 25°C.
[0055] As a preferred solution, the defoaming agent in the reflective heat-insulating color paste, the reflective heat-insulating composite rock sheet and the base paint raw material is any one of the organosilicon defoaming agents.
[0056] As a preferred solution, the pH regulator in the reflective heat-insulating composite rock sheet and the base paint raw material is at least one of sodium hydroxide, ammonia water, potassium hydroxide and diethanol.
[0057] As a preferred solution, the pH regulator in the reflective heat-insulating composite rock sheet and the base paint raw material is sodium hydroxide.
[0058] As a preferred solution, the bactericidal and mildew-proofing agent in the reflective heat-insulating composite rock sheet and the base paint raw material is isothiazolinone or dioxane.
[0059] As a preferred solution, the bactericidal and mildew-proofing agent in the reflective heat-insulating composite rock sheet and the base paint raw material is isothiazolinone.
[0060] As a preferred solution, the polysiloxane in the reflective heat-insulating composite rock sheet and the base paint raw material is at least one of polydimethylsiloxane, hydroxyl-terminated polydimethylsiloxane, polyether-modified polysiloxane and fluorosilicone.
[0061] As a preferred solution, the polysiloxane in the reflective heat-insulating color paste, the reflective heat-insulating composite rock sheet and the base paint raw material is hydroxyl-terminated polydimethylsiloxane.
[0062] As a preferred solution, the colored sand is reflective heat-insulating colored sand.
[0063] The second aspect of the present application provides a method for preparing the above-mentioned reflective heat-insulating rock flake real stone paint, which specifically includes the following steps: S1: Stir the reflective heat-insulating color paste raw material in a high-speed stirring kettle at 1000~1500rpm for 40~60min until it is evenly dispersed, then enter the sand mill for grinding, and remove large particles through a 400~500 mesh sieve to obtain a reflective heat-insulating color paste; S2: Stir the reflective heat-insulating composite rock flake raw material in a high-speed stirring kettle at 1000~1500rpm for 35~45min until it is evenly dispersed, and then enter the sand mill for grinding. After grinding with a machine, an intermediate is obtained, and the intermediate and the reflective insulation color paste are mixed and stirred to create color, and then the reflective insulation composite rock flakes after the reflective insulation color paste is created are obtained through coating, drying, crushing and screening processes; S3: The raw materials of the basic paint are stirred in a high-speed stirring kettle at 1000-1500rpm for 40-60min until they are evenly dispersed to obtain the basic paint, and finally the reflective insulation composite rock flakes after the reflective insulation color paste is created, the basic paint and the colored sand are stirred in a high-speed stirring kettle at 600-800rpm until they are evenly dispersed, and the paint is uniform and has no stratification.
[0064] The third aspect of the present application defines the application of the above-mentioned reflective heat-insulating rock flake real stone paint in commercial building exterior wall coatings, residential area exterior wall coatings, industrial plant exterior wall coatings, and refrigerated building exterior wall coatings.
[0065] The beneficial effects of this application are: 1. The reflective and heat-insulating rock flake real stone paint provided in the present application can not only meet the existing consumers' demand for the beauty and reflective insulation of building exterior wall decoration materials, but also maintain excellent water-repellent, weather-resistant, stain-resistant and self-cleaning properties; in particular, it can maintain excellent reflective performance in high-brightness environments, reduce the water absorption of the coating, improve the hydrophobicity and self-cleaning properties, and effectively avoid the problems of cracking, peeling and reduced reflectivity of existing real stone paints during use, and has very excellent application prospects.
[0066] 2. A reflective and heat-insulating rock flake real stone paint provided in the present application, the added modified titanium-based particles can form a multi-microporous structure with micro-nano particles as the outer wrapping and composite skeleton particles as the inner main body. The existence of this structure can greatly enhance the maintenance effect of the modified titanium-based particles on the surface oxidation molecules, thereby maintaining the oxidation and decomposition effect of the real stone paint surface on organic pollutants during long-term use, thereby achieving the anti-fouling and self-cleaning effect of the real stone paint surface, and the existence of the multi-microporous structure prompts the real stone paint surface to form more gully surface structures, thereby blocking the surface water molecules during long-term use, avoiding the phenomenon of their continuous aggregation to form a continuous surface water layer phase, so that the real stone paint surface cannot promote the penetration of water molecules through the hydration layer, thereby greatly improving its water resistance.
[0067] 3. A reflective and heat-insulating rock flake real stone paint provided in the present application has a complex skeleton structure formed by the added modified titanium-based particles, which can greatly improve the electronic vibration effect of the surface titanium dioxide particles, thereby greatly improving the overall infrared refractive index of the modified titanium-based particles, inhibiting the subsequent conversion efficiency of photothermal energy, and increasing the light penetration resistance through the scattering phenomenon of light, thereby improving the reflection efficiency, and thus obtaining good reflective and heat-insulating properties.
[0068] 4. A reflective and heat-insulating rock flake real stone paint provided in the present application, the added modification additive can achieve the repulsion of water molecules inside the real stone paint through the siloxane and acrylate long chains and corresponding groups it contains, thereby reducing the penetration rate of water and increasing the penetration resistance. On the other hand, it is easier to form a barrier film layer. The presence of this film layer can achieve a barrier effect on water molecules in the system and reduce the humidity of the system. The more solid multi-level cross-linked network formed by it can form microchemical bonds with other raw materials of the real stone paint, fully increasing the mutual viscosity between the molecular chains, thereby greatly improving the resistance of the real stone paint system to molecular chain slippage during use, enhancing the overall toughness and mechanical properties, and reducing the fracture caused by molecular chain slippage, thereby ensuring the anti-cracking and anti-peeling properties of the real stone paint and ensuring the stability of the reflective and heat-insulating properties. DETAILED DESCRIPTION
[0069] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0070] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0071] Example 1 Embodiment 1 The first aspect provides a reflective heat-insulating rock flake real stone paint, the raw materials of which are, by mass percentage: 3.6% reflective heat-insulating color paste, 8.8% reflective heat-insulating composite rock flakes, 28.5% base paint, and the balance is made up of colored sand.
[0072] The raw materials of reflective heat-insulating color paste, calculated by mass percentage, are: 25% reflective heat-insulating pigment, 4.2% dispersant I, 1.8% wetting agent I, 2.1% cellulose ether I, 0.6% defoaming agent I, 2.1% film-forming aid I, 0.4% rheological aid I, and the balance is made up of deionized water.
[0073] Dispersant I is polyvinyl pyrrolidone K30; wetting agent I is ethylene bisstearamide; cellulose ether I is hydroxyethyl cellulose ether; film-forming aid I is dodecyl alcohol ester; rheological aid I is sodium polyacrylate, purchased from Dow Chemical (Shanghai) Co., Ltd., USA, model TT-935.
[0074] The raw materials of reflective heat-insulating composite rock sheet, calculated by mass percentage, are: reflective heat-insulating pigment 8.6%, aluminum silicate 11.4%, composite solid material 28.8%, aqueous acrylic emulsion 32.5%, aqueous polyurethane emulsion 9.1%, cellulose ether ⅠⅠ 0.4%, dispersant ⅠⅠ 0.5%, wetting agent ⅠⅠ 0.16%, pH adjuster 0.22%, defoamer 0.4%, bactericidal and mildewproof agent 0.32%, polysiloxane 0.75%, film-forming aid ⅠⅠ 1.6%, rheological aid ⅠⅠ 0.21%, and deionized water to make up the balance.
[0075] The composite solid material is a composition of talcum powder, heavy calcium carbonate and modified titanium-based particles, and the mass ratio of the three is 8.3:12.5:10.
[0076] The average particle size of talc is 1.8 μm; the average particle size of heavy calcium carbonate is 1.1 μm.
[0077] The preparation method of modified titanium-based particles specifically includes the following steps, calculated by mass: S1: 1.2 parts of titanium dioxide, 0.18 parts of zinc oxide, 0.35 parts of succinic anhydride and 0.08 parts of γ-aminopropylmethyldiethoxysilane are mixed and added to 60 parts of N,N-dimethylformamide solvent, and ultrasonically dispersed at 420W for 30 minutes, then heated to 68°C, ultrasonically kept for 2.2 hours, then centrifuged and filtered, washed with ethanol and dried to obtain pretreated particles; S2: 1.4 parts of pretreated particles, 2.6 parts of tetrabutyl titanate and 2. 4 parts of 1,4-naphthalene dicarboxylic acid are mixed and added to 120 parts of N,N-dimethylacetamide solvent, the temperature is raised to 60°C and ultrasonically dispersed at 450W for 30 minutes, then the temperature is raised to 90°C and kept for reaction for 5.5 hours, 0.45 parts of 2-methylimidazole, 0.5 parts of p-aminobenzoic acid and 0.8 parts of hydrofluoric acid are added, the temperature is raised to 120°C and the reaction is continued for 15 hours; S3: After the reaction is completed, it is cooled to room temperature and centrifuged to obtain a solid product, which is washed twice with N,N-dimethylformamide and deionized water, and then vacuum dried at 80°C for 10 hours.
[0078] The average particle size of titanium dioxide is 12 nm.
[0079] The waterborne polyurethane emulsion has a solid content of 40%, a viscosity of 1500 mPa·s, and a temperature condition of 25° C. The product is a 2606 model purchased from Covestro Polymers (China) Co., Ltd. of Germany.
[0080] Cellulose ether ⅠⅠ is hydroxypropyl methylcellulose ether; dispersant ⅠⅠ is polycarboxylate ammonium salt, purchased from Japan San Nopco Co., Ltd., model SN-5027 product; wetting agent ⅠⅠ is polysorbate 80; film-forming aid ⅠⅠ is hexadecyl acetate; rheological aid ⅠⅠ is 8W model polyurethane rheological aid product sold by Dow Chemical (Shanghai) Co., Ltd.
[0081] The reflective heat-insulating pigment in the reflective heat-insulating color paste and the reflective heat-insulating composite rock sheet raw materials is titanium dioxide W800.
[0082] The raw materials of the base paint, calculated in percentage by mass, are: 49.5% water-based acrylic emulsion, 0.26% pH adjuster, 0.27% bactericidal and mildew-proof agent, 1.8% polysiloxane, 0.3% defoaming agent, 0.8% cellulose ether ⅠⅠⅠ, 2.8% film-forming aid ⅠⅠⅠ, 0.35% rheological aid ⅠⅠⅠ, 0.4% antifreeze agent, 1.4% modification aid, and the balance is made up of deionized water.
[0083] Cellulose ether ⅠⅠⅠ is hydroxyethyl methyl cellulose ether; film-forming aid ⅠⅠⅠ is propylene glycol phenyl ether; rheological aid ⅠⅠⅠ is sodium polyacrylate.
[0084] The antifreeze agent is a composition of diethylene glycol and propylene glycol, and the mass ratio of the two is 4.5:1.2.
[0085] The preparation method of the modified additive specifically includes the following steps, calculated by mass: S1: add 150 parts of deionized water to a high-speed stirrer, stir at room temperature for 6 minutes at a speed of 1000 rpm to ensure that the water temperature is moderate, add 28.8 parts of octamethylcyclotetrasiloxane, heat to 60°C, and stir at a speed of 500 rpm for 30 minutes; S2: after the stirring is completed, add 18.2 parts of aminopropyltriethoxysilane and 5.5 parts of sodium dodecyl sulfate in sequence, adding 500 each time. The mixture was stirred at a speed of rpm for 15 min, and then 8.8 parts of γ-methacryloyloxypropyltrimethoxysilane, 6.2 parts of isobornyl acrylate and 6.8 parts of glycidyl methacrylate were added in sequence and stirring was continued for 30 min. After stirring, the temperature was raised to 85°C, 0.08 parts of benzoyl peroxide were added, and the mixture was kept warm for 4 h. S3: After the reaction was completed, ammonia water was slowly added to control the pH value of the system to 7.8, and then the mixture was naturally cooled to room temperature. The product was filtered through a 550-mesh sieve and washed with ethanol to obtain the product.
[0086] The water-based acrylic emulsion in the reflective heat-insulating composite rock sheet and the base paint raw materials has a solid content of 48%, a viscosity of 2500 mPa·s, and a temperature condition of 25°C. The RS-706T product was purchased from Jiangsu Badfu Technology Development Co., Ltd. in China.
[0087] The defoamer in the reflective heat-insulating color paste, reflective heat-insulating composite rock flakes and base paint raw materials is the organosilicon defoamer BYK-066N.
[0088] The pH regulator in the reflective heat-insulating composite rock flakes and the base paint raw materials is sodium hydroxide.
[0089] The bactericidal and mildew-proofing agent in the reflective heat-insulating composite rock sheet and the base paint raw materials is isothiazolinone.
[0090] The polysiloxane in the reflective heat-insulating color paste, reflective heat-insulating composite rock flakes and base paint raw materials is hydroxyl-terminated polydimethylsiloxane, which was purchased from Wuhan Smack Biotechnology Co., Ltd., China.
[0091] The colored sand is reflective heat-insulating colored sand, purchased from Jiangsu Licai Sand New Materials Co., Ltd., China, and is a pink and white 80-120 product.
[0092] The second aspect of the present application provides a method for preparing the above-mentioned reflective heat-insulating rock flake real stone paint, which specifically includes the following steps: S1: Stir the raw materials of the reflective heat-insulating color paste in a high-speed stirring kettle at 1200rpm for 50min until they are evenly dispersed, then enter the sand mill for grinding, and pass through a 500 mesh to remove large particles to obtain a reflective heat-insulating color paste; S2: Stir the raw materials of the reflective heat-insulating composite rock flakes in a high-speed stirring kettle at 1500rpm for 45min until they are evenly dispersed, then enter the sand mill for grinding to obtain an intermediate, mix the intermediate and the reflective heat-insulating color paste and stir to create color, and then obtain the reflective heat-insulating composite rock flakes after the reflective heat-insulating color paste is created through coating, drying, crushing, and screening processes; S3: Stir the raw materials of the base paint in a high-speed stirring kettle at 1300rpm for 55min until they are evenly dispersed to obtain the base paint, and finally stir the reflective heat-insulating composite rock flakes, the base paint and the colored sand after the reflective heat-insulating color paste are colored in a high-speed stirring kettle at 700rpm until they are evenly dispersed, and the paint is uniform and has no stratification.
[0093] Example 2 The specific implementation method of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the reflective heat-insulating rock flake real stone paint, in terms of mass percentage, are: 2.5% reflective heat-insulating color paste, 9.5% reflective heat-insulating composite rock flakes, 26.5% base paint, and the balance is supplemented by colored sand.
[0094] Example 3 The specific implementation manner of this embodiment is basically the same as that of Example 1, except that: the raw materials of the reflective heat-insulating composite rock sheet, in terms of mass percentage, are: 9.2% reflective heat-insulating pigment, 10.5% aluminum silicate, 24.6% composite solid material, 33.5% aqueous acrylic emulsion, 8.6% aqueous polyurethane emulsion, 0.36% cellulose ether ⅠⅠ, 0.42% dispersant ⅠⅠ, 0.2% wetting agent ⅠⅠ, 0.24% pH adjuster, 0.3% defoamer, 0.38% bactericidal and mildewproof agent, 0.65% polysiloxane, 1.5% film-forming aid ⅠⅠ, 0.3% rheological aid ⅠⅠ, and the balance is supplemented by deionized water.
[0095] The composite solid material is a composition of talcum powder, heavy calcium carbonate and modified titanium-based particles, and the mass ratio of the three is 10:10:8.
[0096] The average particle size of talc is 2 μm; the average particle size of heavy calcium carbonate is 1.5 μm.
[0097] Comparative Example 1 The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the reflective heat-insulating rock flake real stone paint, in terms of mass percentage, are: 5.5% reflective heat-insulating color paste, 4.5% reflective heat-insulating composite rock flakes, 35.5% base paint, and the balance is supplemented by colored sand.
[0098] Comparative Example 2 The specific implementation manner of this comparative example is basically the same as that of Example 1, except that: the base paint, in terms of mass percentage, comprises the following raw materials: 55.5% aqueous acrylic emulsion, 0.26% pH adjuster, 0.27% bactericidal and mildew-proof agent, 1.8% polysiloxane, 0.3% defoaming agent, 0.8% cellulose ether ⅠⅠⅠ, 2.8% film-forming aid ⅠⅠⅠ, 0.35% rheological aid ⅠⅠⅠ, 0.4% antifreeze agent, 0.3% modifying aid, and the balance is supplemented by deionized water.
[0099] Comparative Example 3 The specific implementation of this comparative example is basically the same as that of Example 1, except that in the reflective heat-insulating composite rock sheet, the composite solid material is a composition of talcum powder, heavy calcium carbonate and modified titanium-based particles, and the mass ratio of the three is 20:15:2.
[0100] Comparative Example 4 The specific implementation of this comparative example is basically the same as that of Example 1, except that: in the reflective heat-insulating composite rock sheet, the preparation method of the modified titanium-based particles specifically includes the following steps, calculated by mass: S1: 2 parts of titanium dioxide, 0.35 parts of succinic anhydride and 0.08 parts of γ-aminopropylmethyldiethoxysilane are mixed and added to 60 parts of N,N-dimethylformamide solvent, and ultrasonically dispersed at 420W for 3 minutes, then heated to 68°C, ultrasonically insulated for 2.2 hours, then centrifuged and filtered, washed with ethanol and dried to obtain pretreated particles; S2: 1.4 parts of Pre-treat particles, mix 2.6 parts of tetrabutyl titanate and 2.4 parts of 1,4-naphthalene dicarboxylic acid and add them to 120 parts of N,N-dimethylacetamide solvent, heat to 60°C and ultrasonically disperse at 450W for 30 minutes, then heat to 90°C and keep warm for reaction for 5.5 hours, add 0.5 parts of p-aminobenzoic acid and 0.8 parts of hydrofluoric acid and heat to 120°C and continue to keep warm for reaction for 15 hours; S3: After the reaction is completed, cool to room temperature, centrifuge to obtain a solid product, wash twice with N,N-dimethylformamide and deionize, and then vacuum dry at 80°C for 10 hours.
[0101] Comparative Example 5 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified titanium-based particles specifically includes the following steps, calculated by mass: S1: 0.8 parts of titanium dioxide, 0.8 parts of zinc oxide, 0.35 parts of succinic anhydride and 0.08 parts of γ-aminopropylmethyldiethoxysilane are mixed and added to 60 parts of N,N-dimethylformamide solvent, and ultrasonically dispersed at 420W for 30 minutes, then heated to 68°C, ultrasonically incubated for 2.2 hours, then centrifuged, washed with ethanol and dried to obtain pretreated particles; S2: 2.4 parts of pretreated particles are mixed and added to 60 parts of N,N-dimethylformamide solvent, and ultrasonically dispersed at 420W for 30 minutes, then heated to 68°C, ultrasonically incubated for 2.2 hours, and then centrifuged and filtered, washed with ethanol and dried to obtain pretreated particles; , 2.6 parts of tetrabutyl titanate and 1.8 parts of 1,4-naphthalene dicarboxylic acid are mixed and added to 120 parts of N,N-dimethylacetamide solvent, the temperature is raised to 60°C and ultrasonically dispersed at 450W for 30 minutes, then the temperature is raised to 90°C and kept for reaction for 5.5 hours, 1.5 parts of 2-methylimidazole, 0.2 parts of p-aminobenzoic acid and 0.8 parts of hydrofluoric acid are added and the temperature is raised to 120°C and the reaction is continued for 15 hours; S3: After the reaction is completed, it is cooled to room temperature and centrifuged to obtain a solid product, which is washed twice with N,N-dimethylformamide and deionized water, and then vacuum dried at 80°C for 10 hours.
[0102] Comparative Example 6 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modification aid specifically includes the following steps, calculated by mass: S1: add 150 parts of deionized water to a high-speed stirrer, stir at room temperature for 6 minutes at a speed of 1000 rpm to ensure that the water temperature is moderate, add 28.8 parts of octamethylcyclotetrasiloxane, heat to 60°C, and stir at a speed of 500 rpm for 30 minutes; S2: after the stirring is completed, add 18.2 parts of aminopropyltriethoxysilane and 5.5 parts of sodium dodecyl sulfate in sequence, adding 500 parts each time; The mixture was stirred at a speed of rpm for 15 min, and then 2.2 parts of γ-methacryloyloxypropyltrimethoxysilane, 3.3 parts of isobornyl acrylate and 1.5 parts of glycidyl methacrylate were added in sequence and stirring continued for 30 min. After stirring was completed, the temperature was raised to 85°C, 0.08 parts of benzoyl peroxide were added, and the mixture was kept warm for reaction for 3.5 h. S3: After the reaction was completed, ammonia water was slowly added to control the pH value of the system to 7.8, and then the mixture was naturally cooled to room temperature. The product was filtered through a 550-mesh sieve and washed with ethanol to obtain the product.
[0103] Comparative Example 7 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modification aid specifically includes the following steps, calculated by mass: S1: add 150 parts of deionized water to a high-speed stirrer, stir at room temperature for 6 minutes at a speed of 1000 rpm to ensure that the water temperature is moderate, add 8.5 parts of octamethylcyclotetrasiloxane, heat to 60°C, and stir at a speed of 500 rpm for 30 minutes; S2: after the stirring is completed, add 18.2 parts of aminopropyltriethoxysilane and 5.5 parts of sodium dodecyl sulfate in sequence, adding 500 parts each time; The mixture was stirred at a speed of rpm for 15 minutes, and then 15.5 parts of γ-methacryloyloxypropyltrimethoxysilane, 9.2 parts of isobornyl acrylate and 10.6 parts of glycidyl methacrylate were added in sequence and stirring was continued for 30 minutes. After stirring, the temperature was raised to 85°C, 0.08 parts of benzoyl peroxide were added, and the mixture was kept warm for reaction for 3.5 hours. S3: After the reaction was completed, ammonia water was slowly added to control the pH value of the system to 7.8, and then the mixture was naturally cooled to room temperature. The product was filtered through a 550-mesh sieve and washed with ethanol to obtain the product.
[0104] Performance Evaluation Solar reflectivity test: The solar reflectivity test was performed on the products obtained in the embodiments and comparative examples according to the reference standard JG / T 235-2014. The test values were recorded in Table 1 by taking the average value of 10 tests.
[0105] Near infrared reflectivity test: The near infrared reflectivity test was performed on the products obtained in the examples and comparative examples with reference to the standard JG / T 235-2014. The test values were averaged from 10 tests and recorded in Table 1.
[0106] Water absorption test: The water absorption test was carried out on the products obtained in the embodiments and comparative examples according to the reference standard JG / T 24-2018. The immersion time was 24 h, the immersion medium was distilled water, the temperature was 23±2°C, and the test value was the average value of 10 tests and recorded in Table 1.
[0107] Anti-fouling test: The anti-fouling test was performed on the products obtained in the embodiments and comparative examples according to the standard JG / T 24-2018, and the test rating results were recorded in Table 1.
[0108] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of reflective heat insulation performance, hydrophobic performance and stain resistance. This is mainly because the modified titanium-based particles with the best performance and the modified auxiliary agents with the best compound combination used in the examples can achieve the repulsion of water molecules inside the real stone paint through the siloxane and acrylate long chains and corresponding groups they contain, reduce the penetration rate of water, and increase the penetration resistance. On the other hand, it is easier to form a barrier film layer. The presence of this film layer can achieve a barrier effect on water molecules in the system and reduce the humidity of the system. The more solid multi-level cross-linked network formed by it can form microchemical bonds with other raw materials of the real stone paint, fully increase the mutual viscosity between the molecular chains, thereby greatly improving the resistance of the real stone paint system to molecular chain slippage during use, enhancing the overall toughness and mechanical properties, and reducing the fracture caused by molecular chain slippage, thereby ensuring the anti-cracking and anti-peeling properties of the real stone paint and ensuring the stability of the reflective heat insulation performance.
Claims
1. A reflective heat-insulating rock flake real stone paint, characterized in that: In terms of mass percentage, the raw materials of rock flake real stone paint are: 1-8% reflective heat insulation color paste, 5-15% reflective heat insulation composite rock flakes, 20-35% base paint, and the balance is supplemented by colored sand; The raw materials of the reflective heat-insulating color paste include: 20-30% reflective heat-insulating pigment; The raw materials of the reflective heat-insulating composite rock sheet include: 6-10% reflective heat-insulating pigment, 10-12% aluminum silicate, and 20-30% composite solid material; The composite solid material is a composition of talcum powder, heavy calcium carbonate and modified titanium-based particles, with a mass ratio of (6-10): (10-15): (8-14); The raw materials of the base paint include: 48-50% water-based acrylic emulsion and 0.5-1.5% modification additive; The preparation method of the modified titanium-based particles comprises: S1: adding titanium dioxide, zinc oxide, succinic anhydride and γ-aminopropylmethyldiethoxysilane to a mixture in an N,N-dimethylformamide solvent to obtain pretreated particles; S2: adding the pretreated particles, tetrabutyl titanate and 1,4-naphthalene dicarboxylic acid to a mixture in an N,N-dimethylacetamide solvent, adding 2-methylimidazole, p-aminobenzoic acid and hydrofluoric acid to continue the reaction; S3: cooling after the reaction is completed, centrifugally filtering to obtain a solid product, washing and vacuum drying to obtain the solid product; The preparation method of the modified auxiliary agent comprises: S1: adding octamethylcyclotetrasiloxane into deionized water, heating and stirring; S2: after the stirring is completed, adding aminopropyl triethoxysilane and sodium dodecyl sulfate, γ-methacryloxypropyl trimethoxysilane, isobornyl acrylate and glycidyl methacrylate in sequence, stirring for reaction, adding benzoyl peroxide, and continuing the reaction at a heat preservation temperature; S3: after the reaction is completed, slowly adding ammonia water, controlling the pH value of the system to 7.5-8, and sieving and washing the product after cooling to obtain the modified auxiliary agent.
2. The reflective heat-insulating rock flake real stone paint according to claim 1, characterized in that: The mass ratio of the reflective heat-insulating color paste, the reflective heat-insulating composite rock flakes and the base paint is (2-5): (5-10): (25-30).
3. The reflective heat-insulating rock flake real stone paint according to claim 2, characterized in that: The reflective heat-insulating color paste further comprises, by weight percentage, the following raw materials: dispersant I 3-5%, wetting agent I 1.5-2.5%, cellulose ether I 1-3%, defoamer 0.5-0.8%, film-forming aid I 2-2.5%, rheological aid I 0.3-0.5%, and deionized water to make up the balance.
4. The reflective heat-insulating rock flake real stone paint according to claim 3 is characterized by: The dispersant I is polyvinyl pyrrolidone or polycarboxylate; the wetting agent I is ethylene bis stearamide or polyoxyethylene glyceryl tristearate; the cellulose ether I is at least one of hydroxyethyl cellulose ether, hydroxypropyl cellulose ether and hydroxyethyl methyl cellulose ether; and / or, the film-forming aid I is at least one of dodecyl alcohol ester, hexadecanol ester and sorbitan tristearate; the rheological aid I is organic modified bentonite or sodium polyacrylate.
5. The reflective heat-insulating rock flake real stone paint according to claim 4, characterized in that: The average particle size of the talc powder is 1.5-2 μm; the average particle size of the heavy calcium carbonate is 0.5-1.5 μm.
6. The reflective heat-insulating rock flake real stone paint according to claim 5, characterized in that: The average particle size of the titanium dioxide is 10-15 nm; The mass ratio of titanium dioxide, zinc oxide, succinic anhydride and γ-aminopropylmethyldiethoxysilane is (1-1.2): (0.1-0.2): (0.3-0.4): (0.05-0.1); The mass ratio of the pretreated particles, tetrabutyl titanate, 1,4-naphthalene dicarboxylic acid, 2-methylimidazole and p-aminobenzoic acid is (1.2-1.5): (2.5-3): (2.2-2.6): (0.3-0.5): (0.4-0.6).
7. The reflective heat-insulating rock flake real stone paint according to claim 6, characterized in that: The mass ratio of octamethylcyclotetrasiloxane, aminopropyltriethoxysilane and sodium dodecyl sulfate is (25-30): (15-20): (5-6); The mass ratio of octamethylcyclotetrasiloxane, γ-methacryloxypropyltrimethoxysilane, isobornyl acrylate and glycidyl methacrylate is (25-30): (7-10): (5-8): (5-8).
8. The reflective heat-insulating rock flake real stone paint according to claim 7, characterized in that: The reflective heat-insulating composite rock sheet further comprises, by weight percentage, 30-35% of aqueous acrylic emulsion, 8-10% of aqueous polyurethane emulsion, 0.2-0.5% of cellulose ether ⅠⅠ, 0.3-0.6% of dispersant ⅠⅠ, 0.1-0.2% of wetting agent ⅠⅠ, 0.2-0.3% of pH regulator, 0.3-0.7% of defoamer, 0.3-0.5% of bactericide and mildewproof agent, 0.5-1% of polysiloxane, 1-2% of film-forming aid ⅠⅠ, 0.1-0.3% of rheological aid ⅠⅠ, and the balance is supplemented by deionized water; And / or, the base paint further comprises, by mass percentage, the following raw materials: pH regulator 0.2-0.3%, bactericide and mildew preventer 0.2-0.5%, polysiloxane 1-2%, defoamer 0.2-0.5%, cellulose ether ⅠⅠⅠ 0.6-1%, film-forming aid ⅠⅠⅠ 2.5-3%, rheology aid ⅠⅠⅠ 0.1-0.5%, antifreeze agent 0.2-0.5%, and deionized water to make up the balance; The reflective heat-insulating pigment in the reflective heat-insulating color paste and the reflective heat-insulating composite rock sheet raw material is at least one of titanium dioxide W800, iron oxide yellow, cobalt green, cobalt blue, titanium nickel yellow, zinc iron yellow and chrome iron black.
9. A method for preparing the reflective heat-insulating rock flake real stone paint according to any one of claims 1 to 8, characterized in that: The specific steps include: S1: Stir the raw materials of reflective heat insulation color paste in a high-speed stirring kettle at 1000-1500 rpm for 40-60 min until they are evenly dispersed, then grind them in a sand mill, and remove large particles through a 400-500 mesh sieve to obtain reflective heat insulation color paste; S2: Stir the raw materials of reflective heat insulation composite rock slices in a high-speed stirring kettle at 1000-1500 rpm for 35-45 min until they are evenly dispersed, then grind them in a sand mill to obtain an intermediate, and mix the intermediate with the reflective heat insulation The color paste is mixed and stirred to create color, and then the reflective insulation composite rock flakes after the reflective insulation color paste is created are obtained through coating, drying, crushing and screening processes; S3: the raw materials of the basic paint are stirred in a high-speed stirring kettle at 1000-1500rpm for 40-60min until they are evenly dispersed to obtain the basic paint, and finally the reflective insulation composite rock flakes after the reflective insulation color paste is created, the basic paint and the colored sand are stirred in a high-speed stirring kettle at 600-800rpm until they are evenly dispersed, and the paint is uniform without stratification.
10. Use of the reflective heat-insulating rock flake real stone paint according to any one of claims 1 to 8 in commercial building exterior wall paint, residential area exterior wall paint, industrial plant exterior wall paint, and cold storage building exterior wall paint.
Citation Information
Patent Citations
Composite rock sheet as well as preparation method thereof
CN103571254A
Zirconium n-Butoxide modified high-hardness and abrasion-resisting coating for urban copper-cast sculpture and preparation method thereof
CN105885604A
Rock slice real stone lacquer and preparation method
CN106431078A
Heat-insulating and anti-radiation maishi paint for outer wall
CN107651880A
Anti-fog coating for vehicle-mounted camera and preparation method of anti-fog coating
CN119307173A